Hyperreality dan Self Disclosure Kaum Homoseksual di Twitter - Dhavy Raga Siwi; Poppy Febriana (Jurnal Nomosleca, 2022)
Homosexuals who use the Twitter platform is a hyperreality phenomenon. The media is used to express oneself and gain recognition from society. The purpose of this study is to reveal the hyperreality and self-disclosure of homosexuals through alter accounts on Twitter. The research method uses a qualitative approach with a phenomenological study. The data collection technique is purposive sampling. Data collection techniques through observation, in-depth interviews, literature study, and documentation. The results of the study found thathyperreality that occurs in altering accounts is a simulation of identity on Twitter and the level of self-disclosure which is measured through the dimensions of duration, frequency, valence, honesty, purpose and intent, and intimately, it is found that the openness of altering account users is said to be in a good level and the reason is because of a sense of belonging comfortable and relieved after self-disclosure. Keywords: Hyperreality, Self Disclosure, Twitter